Upper gastrointestinal bleeding in chronic pancreatitis - Kandel, BP; Ghimire, B; Lakhey, PJ; Shrestha, UK; Khakurel, M (Journal of Institute of Medicine Nepal, 2011)
Pseudoaneurysm of peripancreatic vessels is a rare complication of chronic pancreatitis. Being close to the pancreas, splenic artery is the most frequently affected vessel whereas right gastroepiploic artery pseudoaneurysm is very rare. Rupture of such pseudoaneurysm is a rare cause of upper gastrointestinal (GI) bleeding. We report a patient of chronic pancreatitis with past history of pancreatic duct stenting who presented with massive upper GI bleeding and stent migration. Bleeding from pseudoaneurysm of right gastroepiploic artery was detected in angiography. Coil embolization was done but later rebleeding occurred and was managed with laparotomy and ligation of the pseudoaneurysm. Patient improved during postoperative period. Keywords: chronic pancreatitis; embolization; pseudoaneurysm DOI: http://dx.doi.org/10.3126/joim.v32i2.4946 Journal of Institute of Medicine, August, 2010; 32: 47-50